Modern Manufacturing Engineering - Davim, J. Paulo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book covers recent research and trends in Manufacturing Engineering. The chapters emphasize different aspects of the transformation from materials to products. It provides the reader with fundamental materials treatments and the integration of processes. Concepts such as green and lean manufacturing are also covered in this book.
Preface -- Submicro– and nanostructuring of materials by severe plastic Deformation -- Cross rolling: A metal forming process -- A finite element method in machining processes: A review -- Machining and machining modelling of metal matrix composites: A Review -- Intelligent CNC tool path optimization for sculptured surface machining through virus-evolutionary genetic algorithm -- Friction stir welding: Scope and recent developments -- Innovative joining technologies based on tube forming -- Lean manufacturing -- Quantifying quality of learning during teaching an undergraduate unit: Manufacturing processes -- Index.
Keywords: Manufactures; Metals; Ceramics; Glass; Composites (Materials).; Composite materials; Manufacturing, Machines, Tools, Processes; Metallic Materials; Ceramics, Glass, Composites, Natural Materials; Manufacturing, Machines, Tools, Processes